2010
DOI: 10.4314/eajsci.v3i2.53215
|View full text |Cite
|
Sign up to set email alerts
|

Response of Yield and Yield Components of Field Pea to Tillage Frequency, Phosphorus Fertilization and Weed Control on Nitisols of Central Ethiopian Highlands

Abstract: The effects of tillage frequency, phosphorus fertilizer and weed control on yield and yield components of field pea (Pisum sativum L.) were studied in the 2003 and 2004 main cropping seasons on farmers fields in the Chelia and Welmera Districts of west Shewa, Ethiopia. Four levels of tillage frequency (T4 = April, May, early June and at planting; T3 = May, early June and at planting; T2 = May and at planting and T1= at planting) as main plots and factorial combinations of four levels of phosphorus fertilizer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The significant and positive relationship between pods per plant and field The Effect of Plant Density, Zinc Added to Phosphorus Fertilizer Sources and Location on Selected Yield Parameters of Soybean biomass might be attributed to more branches that are able to carry more pods number per plant. This observation confirms the findings of Agegnehu and Beyene (2009) who reported that the results indicated a highly significant positive response of total biomass and number of pods per plant to tillage frequency. The association between 100 seeds weight and field biomass (R 2 = 0.01) was positive and significant.…”
Section: The Correlation Analysis For Three Soybean Yield Variables I...supporting
confidence: 92%
“…The significant and positive relationship between pods per plant and field The Effect of Plant Density, Zinc Added to Phosphorus Fertilizer Sources and Location on Selected Yield Parameters of Soybean biomass might be attributed to more branches that are able to carry more pods number per plant. This observation confirms the findings of Agegnehu and Beyene (2009) who reported that the results indicated a highly significant positive response of total biomass and number of pods per plant to tillage frequency. The association between 100 seeds weight and field biomass (R 2 = 0.01) was positive and significant.…”
Section: The Correlation Analysis For Three Soybean Yield Variables I...supporting
confidence: 92%